Evaluation by an Aeronautic Dentist on the Adverse Effects of a Six-Week Period of Microgravity on the Oral Cavity - Balwant Rai; Jasdeep Kaur; Bernard H. Foing (International Journal of Dentistry)
Objective. HDT bed rest condition is a simulated microgravity condition in which subject lies on bed inclined −6 degree feet up. To determine the influence of a simulated microgravity (HDT bed rest) on oral cavity, 10 healthy male volunteers were studied before, during, just after, and after 6 weeks of the simulated microgravity condition of −6° head-down-tilt (HDT) bed rest. Materials and Methods. Facial nerve function, facial sensation, chemosensory system, salivary biomarkers were measured. Results. Lactate dehydrogenase, MIP 1 alpha, malonaldehyde, 8-hydroxydeoxyguanosine, and thiocyanate were found to increase significantly, while flow rate, sodium, potassium, calcium, phosphate, protein, amylase activity, vitamin E and C, and mouth opening were decreased in simulation environments in contradiction to normal. The threshold for monosodium glutamate (MSG) and capsaicin increased during microgravity as compared to normal conditions. Moderate pain of teeth, facial oedema, mild pain, loss of sensation of pain and temperature, decreased tongue, and mandibular movement in simulation microgravity environments were observed. Conclusions. These results suggest that reversible effect of microgravity is oedema of face, change in taste, abnormal expression of face, teeth pain, and xerostomia. Further study will be required on large scale on long-term effects of microgravity on oral cavity to prevent the adverse effects.